PERANCANGAN SISTEM INFORMASI DATABASE PEMBELIAN DAN PENJUALAN PRODUK PADA SHAVIRA PANCAKE BANDA ACEH - Putra, Furqaan; Fachruddin, Rudy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
Purchase and sales are things which often heard in a company. The use of manual recording results in a number of problems in the company. Seeing the results of purchases, sales and transaction data manually would take a long time. This study aims to design a database of purchases and sales information systems to help employees manage purchase and sale transactions easier, therefore reducing errors and speed up the proccess of transaction calculations. The system designed in this study uses Microsoft Access. This study uses descriptive qualitative method, data collection techniques was done by conducting interviews, observations, and literature studies carried out directly with the owner of the company. This study produces an application system that would ease future corporate activities.